Dissection of a beta-barrel motif leads to a functional dimer: the case of the intestinal fatty acid binding protein - Franchini, Gisela Raquel (2009)
A lingering issue in the area of protein engineering is the optimal design of beta motifs. In this regard, the framework provided by intestinal fatty acid binding protein (IFABP) was successfully chosen to explore the consequences on structure and function of the redesign of natural motifs. A truncated form of IFABP (Delta 98 Delta) served to illustrate the nonintuitive notion that the integrity of the beta-barrel can indeed be compromised with no effect on the ability to attain a native-like fold. This is most likely the outcome of the key role played by the preservation of essential core residues. In the search for the minimal structural determinants of this fold, Delta 98 Delta offered room for further intervention. A dissection of this protein leads to a new abridged variant, Delta 78 Delta, containing 60% of the amino acids of IFABP. Spectroscopic analyses indicate that Delta 78 Delta retains substantial beta-sheet content and preserves tertiary interactions, displaying cooperative unfolding and binding activity. Most strikingly, this construct adopts a remarkably stable dimeric structure in solution. This phenomenon takes advantage of the inherent structural plasticity of this motif, likely profitting from edge-to-edge interactions between beta-sheets, whereas avoiding the most commonly occurring outcome represented by aggregation.